Broad market indices of Nepal Stock Exchange: Testing of efficient market hypothesis - Phulara, Pawan Kumar; Limbu, Naku; Regmi, Sabina; Regmi, Sita; Bajracharya, Rajan Bilas (Academia Journal of Research and Innovation, 2025)
This research evaluates the weak-form efficiency of the Nepal Stock Exchange (NEPSE) by examining 17 broad market indices from January 2021 to May 2025, using daily closing price data. Statistical methods, autocorrelation tests, and run tests, are applied to assess whether price movements follow a random walk, a hallmark of market efficiency where past prices cannot predict future returns. Autocorrelation tests show strong serial correlation (0.821–0.995 at lag 1, p = 0.000), indicating non-stationarity. Run tests confirm random patterns in indices like NEPSE and Mutual Fund (p > 0.05) but non-random behavior in Microfinance, Hydropower, Development Bank, Float, Life Insurance, and Banking (p < 0.05), suggesting inefficiencies. The findings suggest NEPSE is not fully weak-form efficient, presenting opportunities for investors to capitalize on predictable patterns, while policymakers should address liquidity and regulatory challenges to improve market efficiency.